PERSONAL FINANCIAL MANAGEMENT AND ARCHIVAL MANAGEMENT THROUGH MENTORSHIP TO HIGH SCHOOL STUDENTS - Evinita, Lenny Leorina; Paoki, Rouna; Sarahutu, Regina Margaretha (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The purpose of this activity is to provide increased progress for staff and teachers regarding the planning and management of financial and archival documents owned by the school, and also provide basic knowledge to high school students about financial and archival management. This has an impact on improving the quality of financial staff and administrative staff to facilitate and improve the quality of the school. The methods used in this service are lectures, questions and answers, and group discussions, as well as assignments. The results obtained from the discussion were that there is still a need for education to be given to students regarding personal financial management and archival management, ignorance, they think that they are still too young to know these things.